2022
DOI: 10.1371/journal.pone.0259757
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology and in vitro testing of Theobroma cacao extract’s antioxidative activity and its effects on cancer cell survival

Abstract: Theobroma cacao L. is a commercially important food/beverage and is used as traditional medicine worldwide against a variety of ailments. In the present study, computational biology approaches were implemented to elucidate the possible role of cocoa in cancer therapy. Bioactives of cocoa were retrieved from the PubChem database and queried for targets involved in cancer pathogenesis using BindingDB (similarity index ≥0.7). Later, the protein-protein interactions network was investigated using STRING and compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…In the present study, we observed the amelioration of various oxidative stress biomarkers in multiple organs after COE co-treatment with doxorubicin. Moreover, our previous studies also support the efficacy of COE in ameliorating oxidative stress and cancer progression (Patil et al, 2022b;2022a). Emmanuel et al reported that cocoa leaf polyphenolic-rich extract inhibited xanthine oxidase due to the flavonoids and phenolic acids present in the extract (Irondi et al, 2017).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In the present study, we observed the amelioration of various oxidative stress biomarkers in multiple organs after COE co-treatment with doxorubicin. Moreover, our previous studies also support the efficacy of COE in ameliorating oxidative stress and cancer progression (Patil et al, 2022b;2022a). Emmanuel et al reported that cocoa leaf polyphenolic-rich extract inhibited xanthine oxidase due to the flavonoids and phenolic acids present in the extract (Irondi et al, 2017).…”
Section: Discussionsupporting
confidence: 70%
“…We used the CastP tool to predict the largest and best possible binding pocket in both receptors, namely, LOX and XO. The parameters used for the virtual screening of phytochemicals against LOX and XO were selected from earlier similar studies ( Patil et al, 2022b ). The docked conformations obtained were ranked by the binding energy values, the intermolecular interactions were analyzed using Chimera, and publication-quality figures were generated in PyMOL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation